Dose-dependent progression of parkinsonism in manganese-exposed welders. (24th January 2017) - Racette, Brad A.; Searles Nielsen, Susan; Criswell, Susan R.; Sheppard, Lianne; Seixas, Noah; Warden, Mark N.; Checkoway, Harvey
Abstract : Objective: To determine whether the parkinsonian phenotype prevalent in welders is progressive, and whether progression is related to degree of exposure to manganese (Mn)-containing welding fume. Methods: This was a trade union–based longitudinal cohort study of 886 American welding-exposed workers with 1, 492 examinations by a movement disorders specialist, including 398 workers with 606 follow-up examinations up to 9.9 years after baseline. We performed linear mixed model regression with cumulative Mn exposure as the independent variable and annual change in Unified Parkinson Disease Rating Scale motor subsection part 3 (UPDRS3) as the primary outcome, and subcategories of the UPDRS3 as secondary outcomes. The primary exposure metric was cumulative Mn exposure in mg Mn/m 3 -year estimated from detailed work histories. Results: Progression of parkinsonism increased with cumulative Mn exposure. Specifically, we observed an annual change in UPDRS3 of 0.24 (95% confidence interval 0.10–0.38) for each mg Mn/m 3 -year of exposure. Exposure was most strongly associated with progression of upper limb bradykinesia, upper and lower limb rigidity, and impairment of speech and facial expression. The association between welding exposure and progression appeared particularly marked in welders who did flux core arc welding in a confined space or workers whose baseline examination was within 5 years of first welding exposure. Conclusions: Exposure to Mn-containing welding fume may cause a dose-dependent progression of parkinsonism, especially upper limb bradykinesia, limb rigidity, and impairment of speech and facial expression.